95 DOCUMENTATION OF URINARY CATHETER INDICATION AND INSERTION PROCEDURE FOR MEDICAL INPATIENTS AT A UNIVERSITY TEACHING HOSPITAL. (18th November 2021) - McAteer, C; Sullivan, R; McRory, C; O'Domhnaill, O; Murphy, D E; Rehman, M A; Muller, T; Gallagher, M; Miranda, J; Parihar, V; Mulpeter, K
Abstract: Background: Approximately 25% of inpatients have urinary catheters at some point during their hospital stay; over half are deemed inappropriate. This is significant as catheter-associated urinary tract infections (CAUTI) increase morbidity, mortality and length of hospitalisation. Lack of medical documentation and clinician awareness of catheters have been identified as risk factors for inappropriate catheterisation. The aim of this audit was to assess inpatient urinary catheter use among medical inpatients to determine if the indication and insertion procedure were clearly documented. Methods: The audit was conducted over one day and included all medical inpatients aged 18 years and above. Emergency Department and High Dependency patients were excluded. Data was collected using standardised data collection sheets and involved a review of medical/nursing notes. Data was benchmarked against Health Service Executive guidelines. Results: 27 of 132 medical inpatients (20%) had a urinary catheter in situ on the day of audit. 37% (n = 10) had long-term urinary catheters in situ prior to admission and are not considered further. Of the remaining 63% (n = 17), 9 were female (53%), 8 were male (47%), and the average age was 75 years. Indication was documented in nursing notes for 76% and in medical notes for 53%. Indications included monitoring urinary output (29%), urinary retention (24%), sepsis (18%), comfort (6%) and haematuria (6%). Catheter insertion procedure was documented in nursing notes for 59% and in medical notes for 12%. Conclusion: One fifth of medical inpatients had urinary catheters on the day of audit. 63% of these patients did not have a catheter prior to admission. Overall medical documentation of catheter indication and insertion procedure is poor. Better documentation would likely improve clinician awareness of their patient's catheters and prompt earlier review of appropriateness. Education sessions, insertion proforma stickers and catheter review reminder systems are suggested to improve documentation.